Kedudukan Notaris Sebagai Pejabat Umum Ditinjau Dari Konsep Equality Before The Law - Edwar Edwar; Faisal A.Rani; Dahlan Ali (University of Udayana, 2019)
Notary has the authority to make authentic deeds and has authority in making, agreements and stipulations that are required for those concerned to be stated in an authentic deed that if legal problems occur by a notary then the inspection must be obtained from the Honorary Board of Notary. which resulted in the examination contradicting principle equality before the law. After the issuance of Act No. 2 of 2014 Notary Position, notary publication by law enforcers must obtain permission from MKN which creates legal discrimination. The problem examined is how the position of the notary as a witness is related to the deed or letter under the hand made by him to the judicial process. The aim is finding out how the position of the Notary a witness is related to the deed or letter under his hand made against the judicial process. The results his research were the position of the notary a witness related to the deed he made based on the Notary Position Law resulting in legal proceedings being hampered due to waiting for permission from the Honorary Board of Notaries. In connection with the above procedure, it is indicated that the calling of a notary by law enforcers must be licensed by the Honorary Board of Notaries not in accordance with the concept of equality before the law. Notaris memiliki suatu kewenangan dalam membuat akta otentik serta memiliki wewenang dalam pembuatan, perjanjian serta penetapan yang diwajibkan bagi yang berkepentingan yang dinyatakan dalam akta otentik yang apabila terjadi permasalahan hukum yang dilakukan oleh notaris maka untuk pemeriksaannya harus izin dari Majelis Kehormatan Notaris. yang mengakibatkan pemeriksaan tersebut tidak sesuai dengan equality before the law. Setelah keluarnya Undang-Undang Jabatan Notaris Nomor 2 Tahun 2014 , pemanggilan notaris oleh aparat hukum ada izin dari MKN yang menimbulkan diskriminasi hukum. Permasalahannya yang dikaji adalah Bagaimanakah kedudukan notaris sebagai saksi terkait dengan akta atau surat dibawah tangan yang dibuatnya terhadap proses peradilan. Tujuannya adalah Untuk mengetahui bagaimana kedudukan Notaris sebagai saksi terkait dengan akta atau surat dibawah tangan yang dibuatnya terhadap proses peradilan. Hasil penelitiannya adalah kedudukan notaries sebagai saksi terkait dengan akta yang dibuatnya berdasarkan Undang-Undan Jabatan Notaris mengakibatkan proses hukum terhambat akibat menunggu izin dari Majelis Kehormatan Notaris. Sehubungan dengan prosedur tersebut diatas menunjukkan bahwa pemanggilan notaris oleh penegak hukum harus izin dari Majelis Kehormatan Notaris tidak sesuai dengan Konsep equality before the law.